2009
DOI: 10.1111/j.1528-1167.2009.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory effects of gap junction blockers on cerebral cortex seizure‐like activity in rats and mice

Abstract: SUMMARYPurpose: The role of gap junctions in seizures is an area of intense research. Many groups have reported anticonvulsant effects of gap junction blockade, strengthening the case for a role for gap junctions in ictogenesis. The cerebral cortex is underrepresented in this body of research. We have investigated the effect of gap junction blockade on seizure-like activity in rat and mouse cerebral cortex slices. Methods: Seizure-like activity was induced by perfusing with low-magnesium artificial cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…Consistently, substances promoting gap junction communication by intracellular alkalinization (trimethylamine, ammonium chloride) have been found to increase epileptiform activity (K€ ohling et al, 2001;Perez-Velazquez et al, 1994). It should be noted, however, that others have reported proconvulsive effects of gap junction blockade through carbenoxolone (Voss et al, 2009). In this context one has to consider that most gap junction blockers are not specific, i.e., they have many side effects (Rozental et al, 2001) and barely discriminate between connexin isoforms and thus cell types (Giaume et al, 2010;Steinh€ auser and Seifert, 2002).…”
Section: Gap Junction Communication In Epileptic Tissuementioning
confidence: 99%
“…Consistently, substances promoting gap junction communication by intracellular alkalinization (trimethylamine, ammonium chloride) have been found to increase epileptiform activity (K€ ohling et al, 2001;Perez-Velazquez et al, 1994). It should be noted, however, that others have reported proconvulsive effects of gap junction blockade through carbenoxolone (Voss et al, 2009). In this context one has to consider that most gap junction blockers are not specific, i.e., they have many side effects (Rozental et al, 2001) and barely discriminate between connexin isoforms and thus cell types (Giaume et al, 2010;Steinh€ auser and Seifert, 2002).…”
Section: Gap Junction Communication In Epileptic Tissuementioning
confidence: 99%
“…In a Co 2+ epilepsy model, Mylvaganam et al demonstrated that octanol diminishes ictal and interictal discharges [79] . However, paradoxical excitatory effects of gap junction blockers on seizure-like activity induced by low Mg 2+ in rat cortical slices were recently reported by Voss et al They found that quinine and carbenoxolone increase both the frequency and the the amplitude and quinidine increases the frequency of seizure-like events [104] .…”
Section: +mentioning
confidence: 99%
“…C57/BL6 wild-type and Cx36-knockout mice Mefloquine increases SLE frequency and amplitude in WT mice and (4-month-old) these effects are absent in slices from Cx36-knockout mice [104] .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, there are a growing number of experimental studies showing a reduction in seizure severity following pharmacological gap junction blockade (Bostanci and Bagirici 2007;Nassiri-Asl et al 2009). Intriguingly, several studies point to gap junction blockade having the opposite effect (Voss et al 2009;Jacobson et al 2010), suggesting that the relationship between gap junction regulation and seizure propensity is multifaceted. The apparent discrepancies in the literature surrounding the role of gap junctions in seizurogenesis probably reflect two main complicating factors.…”
Section: Introductionmentioning
confidence: 99%